Pengungkapan Diri Siswa Sekolah Menengah dan Implikasinya Bagi Konseling - Herman Nirwana (Universitas Negeri Malang, 2013)
Abstract: Self-disclosure of High School Students and Its Implications on Counseling. This study identifies the self-disclosure of senior high school students and examines how the implications it has on counseling. Using a stratified-random sampling technique, this study involved 127 students, 50 males and 77 females. The data were collected through a questionnaire, adapted from the Sixty-Item Self-Disclosure Questionnaire. The results of descriptive analysis and t-test indicate that the self-disclosure by senior high school students is still of a low level and that there is a difference between male and female students in self-disclosure, whereby the female students were more open. In counseling, counselors are then expected to become target persons by the students in the sense that they should have nice personality and be trustworthy persons.   Abstrak: Pengungkapan Diri Siswa Sekolah Menengah dan Implikasinya Bagi Konseling. Penelitian ini bertujuan untuk mendeskripsikan pengungkapan diri siswa Sekolah Menengah Atas. Sampel yang digunakan sebanyak 127 (50 pria dan 77 wanita) yang dipilih dengan teknik stratified random sampling. Temuan penelitian memperlihatkan bahwa pengungkapan diri siswa tergolong rendah. Secara umum, terdapat perbedaan pengungkapan diri antara siswa pria dan wanita, di mana siswa wanita lebih terbuka daripada siswa pria. Konselor harus menjadi orang yang dipercaya dan disenangi oleh siswa sehingga mampu menjadi target person. Empati konselor merupakan bagian yang esensial dalam hubungan konselor-klien.